El padrón Municipal de Beneficiencia y la geografía oficial de la pobreza sevillana c. 1905 - Villa López, Juan (Espacio Tiempo y Forma. Serie V, Historia Contemporánea, 2004)
Este trabajo se sitúa entre los años 1904-1906 en Sevilla (España). Se estudia el intento en aquellos años de aligerar las graneles listas de acogidos al Padrón Municipal de Beneficiencia por el coste médico y farmacéutico. El Padrón Municipal se denominaba, a principios del siglo XX, al censo en el que estaban inscritas las personas susceptibles de recibir asistencia sanitaria por parte del ayuntamiento. Al conocer las condiciones para la inscripción, prácticamente todos los asalariados sevillanos (y españoles) podrían formar parte del Padrón. La causa principal es evidente: la miseria del jornal del obrero. Además, se analiza la distribución urbana de los acogidos y su concentración en zonas determinadas que configuran una verdadera geografía urbana de la pobreza con una enorme carga política y social. This work is located in ttie years 1904-1906 in the city of Seville (Spain). It is studied how the town council tried, in these years, to diminish the large list ofpeople registered in what wasis called Padrón Municipal de Beneficiencia (Charity Town Census in English) because it was a great cost, medical and pharmaceutical, forthe town public funds, in that époque of shortage and stagnation. The Charity Town Census was defined, at the beginning oflast century as the census in which were registered people susceptible of receive sanitary assistance from the Town Council. Given the conditions for the registration, almost every wageworker in Seville (and Spain), could take part of the Charity Census. The main reason for this situation was obviously the paltry salary of the workers. Furthermore, it is analysed the city distribution ofpeople belonging to the Census and their concentration in particular áreas of the city shaping a true urban geography of poverty, with an enormus political and social content.